Falsely low phosphatidylethanol may be associated with biomarkers of haemolytic disease. Issue 2 (25th November 2022) - Årving, Alexander; Hilberg, Thor; Sovershaev, Michael; Bogstrand, Stig Tore; Høiseth, Gudrun
Abstract: Aims: Falsely lower or even negative phosphatidylethanol (PEth) levels may theoretically be seen in patients with haemolytic diseases, and the present study aimed to elucidate this hypothesis. Methods: PEth and carbohydrate‐deficient transferrin (CDT) from 9893 serum and whole blood samples were included along with markers of haemolysis (i.e. haptoglobin, HbA1c, reticulocytes, LD and Hb). Cases showing discrepancy between PEth and CDT, that is, a low PEth value and a high CDT value, were considered to be possibly caused by falsely lowered PEth despite high alcohol consumption. These cases ( N = 233) were compared to the control group without PEth and CDT mismatch. Results: The levels of haptoglobin were significantly lower in the cases showing low PEth and high CDT (estimate = −0.62, p = 0.002). The levels of HbA1c (estimate = −3.26, p = 0.001) and Hb (estimate = −0.507, p < 0.001) were also significantly lower in this group. These findings indicate haemolytic diseases in the low PEth/high CDT group. There were no significant differences for reticulocytes and LD concentrations between the low PEth/high CDT group and the control group. Conclusions: These results indicate that falsely low PEth values could be associated with markers of haemolytic diseases, although more research is needed to highlight this further.